An investigation on the functional properties of 1400 kg/m3 foamed concrete with calcium stearate - Neo, Yao Yong (2023)
Lightweight foamed concrete (LFC) has become a prominent construction material for years due to its cellular structure, which provides several outstanding features. For instance, high strength-to-weight ratio, excellent thermal insulation properties, sound insulation, etc. These features make it appropriate for usage on floors, walls, and roofs. Unfortunately, LFC is not favourable in a humid environment, especially in Malaysia, characterized by a tropical climate which frequently experiences precipitation, causing high environmental humidity. LFC will tend to absorb more moisture when exposed to a humid environment. Eventually, it disrupted the performance of LFC in terms of its strength, durability, etc. Thus, a water-repellent calcium stearate (CS) is introduced to reduce water penetration and water absorption of LFC. The objectives of this study are to produce the 1400 kg/m3 density of foamed concrete with a ± 50 kg/m3 of acceptable deviation, to obtain the optimum water-cement ratio of LFC and to investigate the effect of CS towards compressive strength and functional properties of LFC. This study was separated into two stages. The first trial mix stage aimed to obtain the optimum water-cement ratio (w/c) for LFC between 0.5 to 0.6 with 0.02 intervals and without adding CS. It was then determined as 0.56 since it provided the highest compressive strength. For the second stage, the actual mix stage, the optimum w/c ratio of 0.56 was utilised to proceed with casting four types of LFC which contain different dosages of CS ranging from 0 % to 1 % with 0.2 % intervals and cured for 7- and 28- days before conducting the tests. The tests included compressive strength, water absorption, thermal conductivity, and sound absorption tests. LFC reached its highest compressive strength with 0.2 % CS, and LFC with 1 % CS has the lowest thermal conductivity, highest sound absorption and noise reduction coefficients. There was just a slight difference in water absorption for these LFC. In a nutshell, the optimum dosage of CS was 1% since it provides LFC with excellent thermal insulation, sound absorption, and noise reduction features. Still, its compressive strength was reduced due to the delay of the hydration process caused by excessive CS. In future, it is recommended to assess the effect of CS on LFC's pore structure and the microstructure to strengthen the dependability of the data obtained in this study.